TEORI AKUNTANSI DAN PERUMUSANNYA: SEBUAH KAJIAN LITERATUR - Debora Desnia; Desy Amelia Sinaga; Gita Sonia Marpaung; Sylvia Anastasya Marpaung; Jufri Darma (Lembaga Pengembangan Kinerja Dosen, 2025)
Accounting theory is a conceptual foundation used to understand, design and evaluate accounting practices in preparing financial reports. This theory consists of a collection of principles, concepts and methods that provide guidance in making accounting decisions as well as in developing financial policies and regulations. The aim of this research is to look at the history of the formulation of accounting theory. In this research the literature study research method is used, namely a data collection method by understanding and studying theories from various literature related to the research.